2013
DOI: 10.4304/tpls.3.1.17-22
|View full text |Cite
|
Sign up to set email alerts
|

"May Allah Not Let You Experience Another Sorrow": Condolence Strategies Used by Lecturers Who Are Native Speakers of Arabic L1 toward Their Colleague Who Is Native Speaker of Hebrew in Hebrew L2

Abstract: Abstract-This research attempts to investigate the condolence strategies used by Arab native speakers (L1) towards a Hebrew (L2) native speaker in Hebrew (L2). Analysis of these strategies was almost based on strategies developed by a number of researchers (Olshtain and Cohen 1983; Elwood, 2004 and Yahia, 2010). The participants in this study were 85 Arab lectures who responded to a college condolence announcement which was addressed to a Hebrew native-speaker colleague who lost his daughter by e-mail. Frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 7 publications
5
10
1
1
Order By: Relevance
“…It means that these utterances revealed society's appreciation for Elizabeth Queen II's dedication as a woman who served her whole life almost 70 years British Society in particular. However, the researcher found the same meanings but different names from the result study (Murad, 2013) study that the participants used a condolence strategy namely the appreciation of the dead which was less frequently used by the participants. This naming was based on the theory used, but the present study still called ending with thoughtful words.…”
Section: Discussion 421 the Types Of Condolence Strategies For The De...mentioning
confidence: 92%
See 1 more Smart Citation
“…It means that these utterances revealed society's appreciation for Elizabeth Queen II's dedication as a woman who served her whole life almost 70 years British Society in particular. However, the researcher found the same meanings but different names from the result study (Murad, 2013) study that the participants used a condolence strategy namely the appreciation of the dead which was less frequently used by the participants. This naming was based on the theory used, but the present study still called ending with thoughtful words.…”
Section: Discussion 421 the Types Of Condolence Strategies For The De...mentioning
confidence: 92%
“…There has been prior research on the use of condolence strategy and illocutionary acts but has a different object of research from this study. First is research on condolence employed in Hebrew by Arab native speakers (L1) towards a Hebrew native speaker (L2) (L2) (Murad, 2013). He examined that 'religious expressions' accounted for 39.8% of the respondents' primary condolence strategy.…”
Section: Introductionmentioning
confidence: 99%
“…This study was supported by (Murad, 2013) who investigated the condolence strategy used in responding to a college condolence announcement which was addressed to a Hebrew native-speaker colleague who lost his daughter by e-mail. It showed that the most frequent strategy used was 'religion expressions'.…”
Section: Introductionmentioning
confidence: 90%
“…The speech act of condolence has also been studied cross-culturally in other language pairs like Arabic versus English (e.g., Al-Khatib & Salem, 2011), Arabic versus Hebrew (e.g., Murad, 2013), and Persian versus English. In Persian, in a comparative study, Lotfollahi and Eslami-Rasekh (2011) focused on the realization patterns of the condolence speech act among Persian-speaking EFL learners by administering a four-item DCT to 80 Iranian EFL university students and comparing the obtained results with Elwood's (2004) findings of American English NSs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The data elicited through the English and Persian DCTs were then analyzed based on the coding scheme developed by Elwood (2004). This coding scheme was especially selected, for it has already been replicated in a number of studies (e.g., Lotfollahi & Eslami-Rasekh, 2011;Murad, 2013) thereby enabling the researchers to compare the findings with previous research outcomes. Elwood (2004) classified the elicited responses for condolences into five types:…”
Section: Data Collection and Data Analysis Proceduresmentioning
confidence: 99%